Policies to promote environmentally sustainable fertilizer use and supply to 2020 - Bumb, Balu L.; Baanante, Carlos A. (International Food Policy Research Institute, 1996)
In the mid-1960s, when projections of global starvation were common, no one questioned the role of mineral fertilizer (plant nutrients, mainly nitrogen, phosphorus, and potassium from inorganic sources) in promoting food production in the food-deficit countries. On the contrary, fertilizer use was an integral part of the technological trinity--improved seed, irrigation, and fertilizer--responsible for bringing about the Green Revolution that helped many densely populated countries, including India and China, achieve food self-sufficiency in the short span of 20 to 25 years. In the early 1990s, however, fertilizer became a target of criticism mainly because of heavy use in the developed countries, where it was suspected of having an adverse impact on the environment through nitrate leaching, eutrophication, greenhouse gas emissions, and heavy metal uptakes by plants. Consequently, fertilizer use per se was mistakenly identified as an enemy of the environment. The authors argue that, although fertilizer use can contribute to environmental contamination unless managed properly, it is often an indispensable source of the nutrients required for plant growth and food production. Fertilizer use will remain an essential component of future strategies for ensuring food security and protecting the natural resource base. In fulfilling that role, however, fertilizer use should be approached differently in the future. Emphasis should be on growth with management rather than on growth per se, so that the broader goals of food security, agricultural growth, and environmental protection are not sacrificed.